DETERMINAN KEPUTUSAN PENGAMBILAN KREDIT (Studi Kasus pada Nasabah KPR Subsidi Bank Aceh Syariah Cabang Langsa) - Syarifah Nanda; Iqlima Azhar; Dewi Rosa Indah (Jurnal Mahasiswa Akuntansi Samudra, 2022)
This study aims to determine the effect of service quality, procedures and regulatory understanding on credit decisions (a case study on subsidized mortgage customers at Bank Aceh Syariah Langsa Branch). The population of this research is customers who take subsidized mortgage housing at Bank Aceh Syariah Langsa City as many as 153 people. The sampling technique used purposive sampling method and in determining the sample used the Slovin formula. Data collection was done by distributing questionnaires to 60 respondents. The data obtained were then analyzed using SPSS (Statistical Package for the Social Science) version 24. The research method used was quantitative research and analyzed using multiple linear regression. The results of this study indicate that service quality has a significant effect on credit decisions at Bank Aceh Syariah. Procedures have a significant effect on credit decisions at Bank Aceh Syariah. Understanding of regulations has a significant effect on credit decisions at Bank Aceh Syariah. Service quality, procedures and understanding of regulations have a significant effect on credit decisions at Bank Aceh Syariah. The result of the coefficient of determination test is the Adjusted R Square value of 0.742. That is, the variables of Service Quality, Procedure, and Regulatory Understanding simultaneously have a significant effect on Credit Decision Making by 74%, while the remaining 26% are influenced by other variables outside this research model.